Performance of newly developed weed-competitive rice cultivars under lowland and upland weedy conditions - Dimaano, Niña Gracel B.; Ali, Jauhar; Sta. Cruz, Pompe C.; Baltazar, Aurora M.; Diaz, Maria Genaleen Q.; Acero, Bart L.; Li, Zhikang (Cambridge University Press, 2017)
Four early-generation backcross populations (BC1F2) derived from one common recipient parental background, Weed Tolerant Rice 1 (‘WTR1’), and four different donor parents (‘Y134’, ‘Zhong 143’, ‘Khazar’, and ‘Cheng Hui-448’) were tested to identify suitable donor and recipient parents for weed competitiveness and to standardize evaluation of the weed-competitive ability in rice. ‘GSR IR2-6’ (G-6) derived from a backcross of WTR1/Y134//WTR1 was selected as the best population and was advanced for phenotypic experiments in the 2014 dry season. The introgression lines (ILs) derived from the G-6 population were evaluated for seed germination and seedling vigor in greenhouse conditions and for weed-competitive ability under field conditions (upland weed-free, upland weedy, and lowland weedy). Parents and checks were included for comparison. Selection pressure for weed competitiveness was relatively stronger in upland conditions than in lowland conditions. After three rounds of selection and based on their relative grain yield performances across conditions, a total of 21 most-promising introgression fixed lines showing superior traits and weed-competitive ability were identified. G-6-L2-WL-3, G-6-RF6-WL-3, G-6-L15-WU-1,G-6-Y16-WL-2, and G-6-L6-WU-3 were the top ILs in lowland weedy conditions, whereas G-6-Y7-WL-3, G-6-Y6-WU-3, G-6-Y3-WL-3, and G-6-Y8-WU-1 were the highest yielding in upland weedy conditions. The use of weed-competitive rice cultivars in African and Asian countries will be a highly effective strategy to reduce production costs and provide alternative solutions to the unavailability of herbicides. Competitive rice varieties will also significantly improve grain yields in aerobic rice systems and can become an important strategy for successful upland rice production.